Strategi Pengembangan Produk dan Komunikasi Pemasaran Dalam Meningkatkan Omset Penjualan di Masa Pandemic Pada PT. Ervamies Makmur Pratama - Diah Lukitasari; Baiq Herdina Septika (Jurnal Pendidik Indonesia (JPIn), 2023)
This study aims to determine the product development  strategy and to determine the communication  system that is run by PT. Ervamies Makmur Pratama during the  covid-19  period.  This  research  uses  a qualitative  case  study  method  that produces  descriptive  data while the data collection techniques  are carried out by observation, interviews, and documentation techniques, product development strategies  and  communication   systems  that  are  carried  out  by  PT.  Ervamies Makmur Pratama to stay afloat in the midst of the covid-19 pandemic, namely the 4P marketing mix (product, promotion, price, and place) and the communication system using offline and online, using sales marketing and Facebook and Whatsapp. The product development  strategy is carried out by PT. Ervamies Makmur Pratama   as  a  promotional   strategy   to  attract buyers/customers   by  holding discounts, discount prices. Based on the research described by the researcher that the strategy and communication   system  carried  out  by  PT.  Ervamies  Makmur  Pratama  sales income has retumed to normal in 2022 and always provides satisfactory service to customers.